Gambaran Tingkat Pengetahuan tentang Anemia dan Kebiasaan Sarapan Pagi pada Remaja Putri SMP N 9 Kota Jambi - Mayuputri, Eysha; Indrawati, Iin; Iswanto, Iswanto (3031-8572, 2024)
Anemia is a condition in which the level of haemoglobin (Hb) in the body is below normal. A person is said to be anaemic if the result of the Hb <12g/dl. This is experienced by adolescents, one of which is caused by unhealthy eating habits, so knowledge is needed to change adolescent behaviour so as not to experience anaemia. to find out the description of the level of knowledge about anaemia and breakfast habits in adolescent girls SMP N 9 Jambi City. this research is a quantitative study with a descriptive design, data collection is done by interviewing and distributing questionnaires. The data analysis used in the study was univariate analysis, which then the results would show the frequency distribution and the variables studied (knowledge of anaemia and breakfast habits). The number of samples in the study was 52 female students. The sampling technique was proportional random sampling. The results of this study obtained that as many as 53.8% of the respondents had insufficient knowledge about anaemia and breakfast habits obtained as many as 75% of the respondents who rarely do breakfast. In this study, it can be concluded that the knowledge about anaemia in SMP N 9 Jambi City is still lacking about anaemia and the importance of breakfast, especially for learning activities and concentration. It is recommended to the school to provide more education about anaemia and the importance of breakfast.